(i) "\\frac{dy}{dt}=1+t^2\\to\\ y(t)=\\int(t^2+1)dt\\to y(t)=\\frac{1}{3}t^3+t+C_1."
We take into account the initial conditions: "y(1)=0\\to C_1 +\\frac{4}{3}=0\\to C_1=-\\frac{4}{3}."
Substitute "C_1 =-\\frac{4}{3}" into "y(t)=\\frac{t^3}{3}+t+C_1. Answer: y(t)=\\frac{1}{3}(t^3+3t-4)."
(ii)
"(t+1)\\frac{dy}{dt}=1-y\\to\\int(\\frac{dy}{1-y})=\\int(\\frac{dt}{t+1})\\to -\\log(y-1)=\\log(t+1)+C_1\\to \\\\ y(t)=\\frac{C_2}{t+1}+1; \\, y(0)=3\\to C_2 +1=3\\to C_2 =2. \\\\Answer:y(t)=\\frac{t+3}{t+1}.\n\n(i) y\\in R; (ii) y\\in(-\\infty,1)\\bigcup(1,+\\infty)"
Comments
Leave a comment